INTERAKSI DOSIS AIR CUCIAN BERAS DAN JENIS MEDIA TANAM TERHADAP PERTUMBUHAN AWAL TANAMAN TERONG ( Solanum melongena L.) - Agung Setya Wibowo (grafting, 2021)
This study aims to determine the effect of the interaction between the dose of rice washing water and the growing media, the effect of the dose of rice washing water on the early growth of eggplant plants (Solanum melongena L). The study used a randomized design of factorial groups repeated 5 times. The dose of rice washing water is divided into 3 levels, namely: 0 ml / plant (A1), 150 ml / plant (A2), 300 ml / plant (A3), planting media consists of 3 levels, namely B1 (soil + pumice), B2 (soil + sand), B3 (soil + sawdust). The results showed that each treatment had a noticeable influence, namely on the treatment (300 ml of rice washing water) and (soil + sawdust) in variable plant height, leaf length, number of leaves, stem diameter.